Supplementation of a grape seed and grape marc meal extract decreases activities of the oxidative stress-responsive transcription factors NF-kappaB and Nrf2 in the duodenal mucosa of pigs - Gessner, Denise; Fiesel, Anja; Most, Erika; Dinges, Jennifer; Wen, Gaiping; Ringseis, Robert; Eder, Klaus; Justus Liebig University Giessen (My University, 2013)
BACKGROUND:In pigs, enteric infections and the development of gut disorders such as diarrhoea are commonly observed, particularly after weaning. The present study investigated the hypothesis that feeding a grape seed and grape marc extract (GSGME) as a dietary supplement has the potential to suppress the inflammatory process in the small intestine of pigs by modulating the activities of NF-kappaB and Nrf2 due to its high content of flavonoids. METHODS:Twenty-four crossbred, 6 weeks old pigs were randomly assigned to 2 groups of 12 animals each and fed nutritionally adequate diets without or with 1% GSGME for 4 weeks. RESULTS:Pigs administered GSGME had a lower transactivation of NF-kappaB and Nrf2 and a lower expression of various target genes of these transcription factors in the duodenal mucosa than control pigs (P<0.05). Concentrations of alpha-tocopherol and thiobarbituric acid reactive substances (TBARS) in liver and plasma and total antioxidant capacity of plasma and relative mRNA abundances of NF-kappaB and Nrf2 target genes in the liver did not differ between the two groups. However, the ratio of villus height:crypt depth and the gain:feed ratio was higher in the pigs fed GSGME than in control pigs (P<0.05). CONCLUSIONS:This study shows that dietary supplementation of a polyphenol rich GSGME suppresses the activity of NF-kappaB in the duodenal mucosa of pigs and thus might provide a useful dietary strategy to inhibit inflammation in the gut frequently occurring in pigs. Feeding GSGME did not influence vitamin E status and the antioxidant system of the pigs but improved the gain:feed ratio. In overall, the study suggests that polyphenol-rich plant extracts such GSGME could be useful feed supplements in pig nutrition, in order to maintain animal health and improve performance.
Keywords: NF-kappaB; Nrf2; olyphenol; pig; intestine; ddc:630